UJI KETAHANAN TERHADAP ALUMINIUM DAN pH RENDAH PADA JAGUNG (Zea mays L) VARIETAS PIONEER DAN SRIKANDI SECARA IN VITRO - Sri Romaito Dalimunthe; Abdullah Bin Arif; Irpan Badrul Jamal (Jurnal Pertanian Tropik, 2015)
One effort to increase maize productivity is by using marginal land for maize plantation. The marginal land that can be used is acid soil, but the problem are Al toxicity and low pH. To cope with these problems, cultivars having tolerance to Al toxicity and low pH are needed. Plant material used in this research were two maize varieties (Pioneer and Srikandi). Media selection is used there are 4 doses treatment aluminium (0, 250, 500 and 750 ppm AlCl3). All variables were observed except at the variable width of the leaf in this results showed that the treatment of aluminium (AlCl3) would not influence. Treatment combination Variety Srikandi and 250 ppm AlCl3 produces plant height, leaf length and leaf width is the shortest compared to other treatments. Variety Pioneer and Srikandi are suspected of varieties resistant aluminum and low pH values based on relative root length.